Population dynamics of a whip fin silverbiddy gerres filamentosus cuvier, 1829 from the parangipettai waters, southeast coast of india - Sivashanthini, K. (University of Jaffna, 2009)
The present study was undertaken to get information on the maximum size, age and growth parameters and mortality of Gerres filamentosus. The length frequency data were grouped sex wise into 1 cm class intervals, sequentially arranged for two years and used for estimation of growth and mortality. L∞ and K values were obtained by electronic length frequency analysis of computer based method. Value of ‘t0’ (age at ‘0’ length) was estimated by substituting the L∞ and K in the Pauly’s empirical equation. Natural mortality was estimated using Pauly’s method. Fishing mortality rate (F) was calculated from the F = Z – M relationship. The asymptotic length (L∞) and growth coefficient (K) were found to be 26.9 cm and 1.45•year-1 , respectively in males, and 27.11 cm and 1.50•year-1 in females. The ‘t0’ values estimated by substituting the L∞ and K in Pauly’s equation were - 0.1109 in males and -0.1073 in females. Instantaneous rates of mortality (Z) estimated by length converted catch curve for male and female were 3.14 and 3.27. Natural mortality (M) estimated by Pauly’s empirical equation for male and female were 2.41 and 2.47 and the estimated fishing mortality for male and female were 0.73 and 0.80, respectively. The computed current exploitation ratios (E) were 0.23 and 0.24. It is concluded that because computed current exploitation rates (E) are lower than the predicted E, the stock is not overexploited and the fishing pressure on the stock is not excessive. As the G. filamento-sus is exploited under this condition, below the optimum level indicating scope of slight increase in efforts.